2015
DOI: 10.3109/15569527.2015.1067818
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous anthrax: evaluation of 28 cases in the Eastern Anatolian region of Turkey

Abstract: Anthrax is still a serious public health problem in Turkey. Cutaneous anthrax must always be kept in mind when characteristic lesions such as a painless ulcer with vesicles, edema, and a history of contact with animals or animal products are observed in an individual. Early and correct diagnosis significantly affects course of the disease. Protective precautions such as vaccination of animals against anthrax and education of the population would reduce the incidence of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
2
12
1
Order By: Relevance
“…Our study demostrated a similar time pattern as reported in the literature, with the majority of the cases occurring in summer and autumn [9]. Similar to previous studies, exposed skin sites such as the hands, forearms and fingers were mostly affected following a minor abrasion [2,10,11].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our study demostrated a similar time pattern as reported in the literature, with the majority of the cases occurring in summer and autumn [9]. Similar to previous studies, exposed skin sites such as the hands, forearms and fingers were mostly affected following a minor abrasion [2,10,11].…”
Section: Discussionsupporting
confidence: 86%
“…In the majority , there was a history of contact with an infected animal or animal products. People are usually exposed to infectious anthrax agent while harvesting crops, butchering/slaughtering animals, processing/handling meat, cutting meat and skinning [2][3][4][5][6][7]. Our study demostrated a similar time pattern as reported in the literature, with the majority of the cases occurring in summer and autumn [9].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Despite painless pruritic papule and animal exposure history is very typical for the diagnosis, the diagnosis of cutaneous anthrax requires suspicion. Definitive diagnosis is set by gram stain and microbiological analysis of lesion [6]. Painless papule and vesicles are well defined as clinical findings.…”
Section: Discussionmentioning
confidence: 99%